2021
DOI: 10.1101/2021.05.07.443169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glycocalyx crowding with synthetic mucin mimetics strengthens interactions between soluble and virus-associated lectins and cell surface glycan receptors

Abstract: Membrane-associated mucins protect epithelial cell surfaces against pathogenic threats by serving as non-productive decoys that capture infectious agents and clear them from the cell surface and by erecting a physical barrier that restricts their access to target receptors on host cells. However, the mechanisms through which mucins function are still poorly defined due to a limited repertoire of tools available for tailoring their structure and composition in living cells with molecular precision. Using synthe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, based on examining the effect of the wash step, we believe the low MW synMUCs are more readily lost by agitation of the membrane and likely do incorporate similarly to the others. These data were unexpected since Godula et al reported higher efficiency incorporation for a 30mer glucosylated PEG vs. a 140mer or 440mer (Honigfort et al, 2021). The discrepancy could potentially be due to the polymer structure, which in our case is inherently more rigid, the cell type employed, which in their case was red blood cells which have a compact and minimal glycocalyx and do not endocytose, or the structural differences in the cholesterol structures used.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…However, based on examining the effect of the wash step, we believe the low MW synMUCs are more readily lost by agitation of the membrane and likely do incorporate similarly to the others. These data were unexpected since Godula et al reported higher efficiency incorporation for a 30mer glucosylated PEG vs. a 140mer or 440mer (Honigfort et al, 2021). The discrepancy could potentially be due to the polymer structure, which in our case is inherently more rigid, the cell type employed, which in their case was red blood cells which have a compact and minimal glycocalyx and do not endocytose, or the structural differences in the cholesterol structures used.…”
Section: Discussionmentioning
confidence: 54%
“…Study of the cellular glycocalyx is a rapidly growing area in need of tools to precisely probe molecular structure-function relationships. Cell-surface engineering with synthetic mucinmimetic materials has emerged as a strategy which has already provided insights on glycocalyx mechanics, cancer biology, and infection (Paszek et al, 2014;Huang et al, 2017;Delaveris et al, 2020;Honigfort et al, 2021). Though various materials have been used as mucin mimics, a common engineering strategy has been used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation